2019
DOI: 10.1186/s12889-019-6513-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct trajectories of physical activity and related factors during the life course in the general population: a systematic review

Abstract: Background In recent years, researchers have begun applying a trajectory approach to identify homogeneous subgroups of physical activity (PA) in heterogeneous populations. This study systematically reviewed the articles identifying longitudinal PA trajectory classes and the related factors (e.g., determinants, predictors, and outcomes) in the general population during different life phases. Methods The included studies used finite mixture models for identifying trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
142
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(168 citation statements)
references
References 80 publications
19
142
6
1
Order By: Relevance
“…A recent systematic review [12] found most studies identified three to five physical activity trajectories, which differs from the 6 distinct life-course trajectories identified in the current study. The six identified trajectories reflect plausible experiences of physical activity level throughout the life-course.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…A recent systematic review [12] found most studies identified three to five physical activity trajectories, which differs from the 6 distinct life-course trajectories identified in the current study. The six identified trajectories reflect plausible experiences of physical activity level throughout the life-course.…”
Section: Discussioncontrasting
confidence: 83%
“…We first identified the potential number of trajectories that may fit the model based on previous literature. A recent systematic review noted the most common number of trajectories of physical activity across the life-course were 3-5 [12]. We tested models with up to 7 trajectories.…”
Section: Defining Physical Activity Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The inconsistent findings may be due to a wide range of ages or differences in methodology or measurements. 26 The consistently moderate TV-time (2 h/d) class was found to be the most prevalent (48.3%), which slightly differs with the previous result showing that the mean daily TV time in 2015 was 2 hours and 54 minutes per day for Finnish adults aged 25-44 years. 27 Our study found a smaller proportion of adults in the consistently high TV-time class and a larger proportion of adults in the consistently low TVtime class compared with the previous trajectory studies examining youth only.…”
Section: Discussioncontrasting
confidence: 78%
“…However, international [7] and national [8] studies have shown that the majority of young people do not achieve the recommended physical activity levels to confer health bene ts [9]. Furthermore, participation rates in physical activity tend to decrease throughout childhood, with particularly steep declines observed during adolescence [10,11]. For example, national trends in Finland suggest that 45% of 11-year old students meet guideline levels for physical activity, while only 19% of 15-year olds achieved these levels [8].…”
Section: Introductionmentioning
confidence: 99%